Litthabitellidae: a new family of the Truncatelloidea (Mollusca: Caenogastropoda). Issue 5 (15th February 2023) - Falniowski, Andrzej; Jaszczyńska, Aleksandra; Osikowski, Artur; Hofman, Sebastian
ABSTRACT: The gastropod genus Litthabitella Boeters, 1970, type species L. chilodia Westerlund, 1886, inhabits mainly freshwater springs in the coastal regions of the Balkan Peninsula from Greece to Slovenia, southern Italy and the Ionian Islands. These snails are minute and show several synapomorphic character states, such as: broadly ovate osphradium, gonopore deep inside the mantle cavity, thickened circular oviduct, distal termination of the penis wide with a sharp and short lateral filament and two flat, cockscomb-like, four-folded lobes. These characters justify a family rank for the taxon. Three molecular loci – mitochondrial cytochrome oxidase subunit I, nuclear 18S and histone H3 – also confirm the distinctiveness of the Litthabitellidae fam. nov. Analysis of molecular data indicates an estimated time of origin in the Late Miocene (Tortonian) and supports its position as the sister clade of the Hydrobiidae. The shells, protoconchs, radulae, operculum, some histology, female reproductive organs and penis are herein illustrated and described. Molecular data presented for 10 studied populations, confirmed partly by morphological characters, indicate four distinct taxa of species rank. Three species are described: Litthabitella aquaadcrucem sp. nov., Litthabitella cetinensis sp. nov. and Litthabitella levkadensis sp. nov. http://www.zoobank.org/urn:lsid:zoobank.org:pub:A8E1F6A7-EEAE-4B8D-A82D-19A7144283C6 http://www.zoobank.org/urn:lsid:zoobank.org:pub:2ABE7402-A94B-4289-BD15-E98F5C147B2E http://www.zoobank.org/urn:lsid:zoobank.org:pub:10089647-36C6-4773-8E7F-AA0D5BB02833 http://www.zoobank.org/urn:lsid:zoobank.org:pub:714ABC27-992E-454F-B8A6-1006A5BD7D2A